2006
DOI: 10.2337/db06-0035
|View full text |Cite
|
Sign up to set email alerts
|

Common Hepatic Nuclear Factor-4α Variants Are Associated With High Serum Lipid Levels and the Metabolic Syndrome

Abstract: Hepatic nuclear factor-4␣ (HNF-4␣), a transcription factor involved in the regulation of serum lipid and glucose levels, has recently been associated with type 2 diabetes. The HNF-4␣ gene (HNF4A) resides on chromosome 20q12-q13.1, which, in addition to type 2 diabetes, has also previously been linked to high triglycerides in Finnish familial combined hyperlipidemia (FCHL) families. FCHL, characterized by elevated levels of serum total cholesterol, triglycerides, or both, is a common dyslipidemia observed in up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 47 publications
7
47
0
1
Order By: Relevance
“…Taking into consideration that we observed signifi cant gender differences in heritability estimates for TRIGs and in obesity levels, future studies should test for similar HNF4A associations in an independent sample of African ancestry women and those with a wider range in body weight. Nonetheless, similar to our fi ndings, another family study showed that rs3212198 was associated with TRIG in families of European and Mexican ancestry ( 42 ).…”
Section: Discussionsupporting
confidence: 78%
“…Taking into consideration that we observed signifi cant gender differences in heritability estimates for TRIGs and in obesity levels, future studies should test for similar HNF4A associations in an independent sample of African ancestry women and those with a wider range in body weight. Nonetheless, similar to our fi ndings, another family study showed that rs3212198 was associated with TRIG in families of European and Mexican ancestry ( 42 ).…”
Section: Discussionsupporting
confidence: 78%
“…Two of these regions, 3p26.1 to 3p13 and 20p11.21 to 20q13.32, are located near genes which have been previously associated with either free fatty acid or triglyceride levels in FCHL cohorts. 19,20 No evidence for linkage was obtained for the region containing the SCD1 gene on chromosome 10 ( Figure 1). Additional adjustment of the desaturation index for triglyceride and HDL-C levels did not significantly alter the results (Figure 1 The strongest evidence for linkage was located on chromosome 3 near the PPAR-␥ gene (zϭ2.7, Pϭ0.003).…”
Section: Resultsmentioning
confidence: 99%
“…5). In addition to IBD, human HNF4A variants are associated with metabolic syndrome (Weissglas-Volkov et al 2006) and type 2 diabetes (Ma et al 2016). Interestingly, microbiota have also been implicated in both of these diseases (Qin et al 2012;Vrieze et al 2012), raising the possibility that microbiota suppression of HNF4A trans activity could play a role in these diseases as well.…”
Section: Discussionmentioning
confidence: 99%